CONCEPTUAL BASES OF LIFELONG SPIRITUAL EDUCATION AND THE DEVELOPMENT OF IDEOLOGICAL COMPETENCE OF STUDENTS - Qodirov, Q. (FAN va JAMIYAT, 2020)
This article is devoted to modern types, methods, its application, development and effectiveness in the modernization of ideological education in the High Education system in the new Uzbekistan.